Proposta de diagnóstico da inovação e competitividade no setor de serviços - Dalla Nora, Lissandro Dorneles (2011)
Given the context of a growing stake in the Brazilian economy's service sector, contributing to increased competitiveness, innovation in services is an issue that demands to be studied in greater depth and understanding. On the way to work together to advance the number of searches is that this work was proposed to develop a proposal for diagnosis of innovation and competitiveness in the service sector. To meet this objective the research developed in the literature review in a comprehensive, covering the terms of service, innovation and competitiveness, with an integrated knowledge base of the proposal. The research strategy adopted was to action research, a qualitative analysis for the study of the unit under investigation. The proposed diagnosis developed seeks to direct the model presented by the Center for Innovation and competitiveness in the sector under study, and development geared to the five factors: Production, Technology, Human Resources, Finance and Marketing. After having constructed the model and its application demonstrated dynamically, its validity, presenting as a diagnostic tool productive and practical to support consultants and managers in evaluating global companies, allowing also analyze the performance of the company in developing a competitive positioning considering all the dimensions given in the diagnosis. This work eventually helped to fill the gap identified by articulating a set of reports related to services in the development of the proposed diagnosis.